2011
DOI: 10.5565/publmat_55211_09
|View full text |Cite
|
Sign up to set email alerts
|

Metric properties of Outer Space

Abstract: ABSTRACT. We define metrics on Culler-Vogtmann space, which are an analogue of the Teichmüller metric and are constructed using stretching factors. In fact the metrics we study are related, one being a symmetrised version of the other. We investigate the basic properties of these metrics, showing the advantages and pathologies of both choices.We show how to compute stretching factors between marked metric graphs in an easy way and we discuss the behaviour of stretching factors under iterations of automorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
171
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(175 citation statements)
references
References 13 publications
1
171
0
3
Order By: Relevance
“…pour tout γ ∈ Γ 0 et tout x ∈ X. Nous montrons que cette borne supérieure est atteinte sur une partie finie F de Γ 0 {1} indépendante de X et de ρ, ce qui généralise un résultat non publié de T. White sur l'outre-espace, dont une preuve a été donnée par S. Francaviglia et A. Martino [9]. Nous en déduisons le résultat suivant.…”
Section: Stratégie De Démonstrationunclassified
See 2 more Smart Citations
“…pour tout γ ∈ Γ 0 et tout x ∈ X. Nous montrons que cette borne supérieure est atteinte sur une partie finie F de Γ 0 {1} indépendante de X et de ρ, ce qui généralise un résultat non publié de T. White sur l'outre-espace, dont une preuve a été donnée par S. Francaviglia et A. Martino [9]. Nous en déduisons le résultat suivant.…”
Section: Stratégie De Démonstrationunclassified
“…Le point (3) de la proposition 4.1 affirme que cette inégalité est une égalité et que la borne supérieure dans le terme de gauche est atteinte sur un sous-ensemble fini F indépendant de ρ. Dans le cas particulier où ρ est injectif d'image discrète et cocompacte, ce résultat est équivalent à un résultat de T. White obtenu en étudiant une certaine "distance asymétrique" sur l'outre-espace ( [9], prop. 3.15) : nous renvoyons à la partie 6 pour plus de détails.…”
Section: Notons Que Pour Tout éLémentunclassified
See 1 more Smart Citation
“…Bestvina was perhaps the first to suggest transporting this idea to Outer space, and a nice account of the basic properties of this metric can be found in his 2012 PCMI lecture notes [7], where he attributes some of these as unpublished results of his former student Tad White. Francaviglia and Martino published the first systematic study of this metric in [17].…”
Section: The Lipschitz Metric On Outer Spacementioning
confidence: 99%
“…Francaviglia and Martino [17] studied basic properties of both the Lipschitz metric and its symmetized version, and found that the unsymmetrized version has a number of advantages over the symmetrized one. Perhaps the greatest of these is that CV n is geodesically complete in the unsymmetrized version, but is not in the symmetrized one.…”
Section: Geodesics In the Lipschitz Metricmentioning
confidence: 99%